Clinical Performance of Direct Anterior Composite Restorations Using Esthetic Dual-Shade versus Polychromatic Natural Layering Technique: a split mouth randomized controlled clinical trial - Elzayat, Ghada Ahmed; Elsayed, Mai Elsayed; El Zoghby, Amira (Brazilian Dental Science, 2020)
Objective: to evaluate the clinical performance of the dual shade layering and polychromatic resin composite layering techniques using a randomized controlled trail. Material and Methods: 42 participants (84 restorations) of class IV or class III through and through within a pair of anterior contra-lateral teeth were randomly allocated into two groups according to technique of composite restoration placement: control “polychromatic layering” and intervention “dual-shade layering”. Follow-up was done at 1 month (baseline) and 1 year. Restorations were evaluated using Visual Analog Scale (VAS), restoration color shade match using Vita Easyshade V ®, and blinded assessor using FDI criteria for assessment of dental restorations measuring (aesthetic properties). Chi-square test was used to compare between restorations of both techniques. Results: There was no statistically significant difference between restorations of both techniques for patient satisfaction outcome, restorations color match outcome, and for all tested FDI outcomes except surface luster with 100% success. Conclusion: Both dual-shade layering and polychromatic natural layering techniques, exhibited acceptable clinical and esthetic performance. Keywords Composite; Polychromatic layering technique; Dual-shade layering technique; Clinical performance.